The Relationship Between Professional Competencies Instructor With Learning Outcomes For Sewing Training Participants in Rumah Pintar, Sarolangun District - Yolanda, Nova; Ismaniar, Ismaniar (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research was motivated by the low learning outcomes of sewing training participants in rumahpintar in Sarolangun Regency. This is thought to be due to the instructor's poor professionalcompetence, resulting in low learning outcomes for the training participants. This research aims to: 1)Find out the professional competence of instructors in sewing training participants in rumah pintar inSarolangun district. 2) Find out the learning outcomes of sewing training participants in theSarolangun district smart home. 3) Knowing the relationship between the professional competence ofinstructors and the learning outcomes of sewing training participants in rumah pintar in Sarolangundistrict. This type of research is quantitative with a correlational type of research. The population inthis study was 30 people and the sample taken was 20 people with sampling using a simple randomsampling technique. The data collection technique uses a questionnaire. Data analysis techniques usepercentage and rank order formulas.The results of the research show that: 1) The description of theprofessional competence of instructors for sewing training participants in rumah pintar in SarolangunRegency is categorized as poor; 2) The description of learning outcomes for sewing trainingparticipants in rumah pintar in Sarolangun Regency is categorized as very low; 3) There is a significantrelationship between the instructor's professional competence and the learning outcomes of sewingtraining participants in rumah pintar in Sarolangun Regency.The research suggestions are: 1) It ishoped that instructors will improve their professional competence so that they can support betterlearning; 2) It is hoped that training participants can improve learning outcomes to the maximum bybeing active in learning and receiving learning from training; 3) It is hoped that future researchers willexamine new variables so that they can add to existing variables and complete them.Keywords: Instructor Professional Competencies, Learning Outcomes